1999
DOI: 10.1098/rstb.1999.0504
|View full text |Cite
|
Sign up to set email alerts
|

Control of NF–κB transcriptional activation by signal induced proteolysis of IκBα

Abstract: In unstimulated cells the transcription factor NF-kappa B is held in the cytoplasm in an inactive state by I kappa B inhibitor proteins. Ultimately activation of NF-kappa B is achieved by ubiquitination and proteasome-mediated degradation of I kappa B alpha and we have therefore investigated factors which control this proteolysis. Signal-induced degradation of I kappa B alpha exposes the nuclear localization signal of NF-kappa B, thus allowing it to translocate into the nucleus and activate transcription from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 100 publications
3
61
0
Order By: Relevance
“…21 In addition, it is also postulated that SUMOylation of IB␣ is a nuclear event to titrate out nuclear NF-B. 42 We first demonstrated that SUMO-1 antagonizes MEKK1-mediated NF-B activation (Figure 5A), confirming the already published role of SUMO-1 in down-regulating cytokineinduced NF-B activation.…”
Section: Discussionsupporting
confidence: 72%
“…21 In addition, it is also postulated that SUMOylation of IB␣ is a nuclear event to titrate out nuclear NF-B. 42 We first demonstrated that SUMO-1 antagonizes MEKK1-mediated NF-B activation (Figure 5A), confirming the already published role of SUMO-1 in down-regulating cytokineinduced NF-B activation.…”
Section: Discussionsupporting
confidence: 72%
“…Alternatively, the increased NF-B inducibility may be caused by altered degradation of IB-␣. Recent studies demonstrate involvement of ubiquitin-like protein SUMO-1 in a reversible modification of IB-␣ and negative regulation of NF-B activation (26). In addition, NF-B activation can be regulated at the level of nuclear export of the p50/65 IB-␣ complexes by virtue of nuclear shuttling of IB-␣ (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…They block NF-κB nuclear localization sequences and thus cause its cytoplasmic retention [33,34]. Numerous IκBs have been identified; there are three typical IκB proteins, IκB [35], IκB [36] and IκB [37], and two atypical IκB proteins, Bcl-3 [38] and IκB , which act in a different way [39]. The precursor proteins p100 (NFKB2) and p105 (NFKB1) also act as inhibitory molecules [40].…”
Section: Molecular Pathway Of Nf-κb and Its Activationmentioning
confidence: 99%